2016
DOI: 10.1055/s-0042-109066
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Ischemic Preconditioning in Resistance Exercise Fade Over Time

Abstract: This study evaluated the effect of ischemic preconditioning (IPC) on resistance exercise performance in upper limbs. After 12-RM load determination, 21 men attended 4 trials separated by 3 days in a randomized crossover design: IPC (4×5-min occlusion 220 mmHg/reperfusion 0 mmHg) in arms and in thighs, and SHAM (equal to the IPC protocol but "occlusion" at 20 mmHg) in arms and in thighs. 8 min following the respective interventions, the subjects performed one set of resistance exercise in elbow flexion with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
67
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(84 citation statements)
references
References 35 publications
12
67
1
4
Order By: Relevance
“…Portanto, análises mais holísticas 28,30 e específicas ao subtipo de modalidade [31][32][33][34][35] são desejáveis. Outro ponto ressaltado em alguns estudos é que o efeito do IPC poderia ter base motivacional 18,20 , visto que alguns deles mostram que a aplicação da manobra de IPC repetidas vezes minimiza o desempenho físico 19,36 ao longo do tempo. O efeito placebo, altamente reconhecido em estudos sobre o desempenho humano 37 , portanto, precisa ser controlado e considerado na interpretação e tomada de decisão sobre qualquer estratégia 19,25 .…”
Section: Métodos De Investigação E Interpretação Dos Resultadosunclassified
“…Portanto, análises mais holísticas 28,30 e específicas ao subtipo de modalidade [31][32][33][34][35] são desejáveis. Outro ponto ressaltado em alguns estudos é que o efeito do IPC poderia ter base motivacional 18,20 , visto que alguns deles mostram que a aplicação da manobra de IPC repetidas vezes minimiza o desempenho físico 19,36 ao longo do tempo. O efeito placebo, altamente reconhecido em estudos sobre o desempenho humano 37 , portanto, precisa ser controlado e considerado na interpretação e tomada de decisão sobre qualquer estratégia 19,25 .…”
Section: Métodos De Investigação E Interpretação Dos Resultadosunclassified
“…Marocolo et al (2016a) also reported that IPC and SHAM conditions resulted in significantly greater repetitions versus the control condition on the first and second sets, but not on the third set during leg extension at a 12 RM load 24) . Furthermore, the authors reported that the number of repetitions during elbow flexion exercise significantly increased in the early sets, but they tended to decrease over four trials 25) . These two studies suggest that IPC has minor beneficial effects, but these apparently fade over time and may possibly have a placebo effect because, compared with control (CON), the SHAM condition also improved repetitions along with IPC 24,25) .…”
Section: Sprint (Cycle) Performancementioning
confidence: 98%
“…Furthermore, the authors reported that the number of repetitions during elbow flexion exercise significantly increased in the early sets, but they tended to decrease over four trials 25) . These two studies suggest that IPC has minor beneficial effects, but these apparently fade over time and may possibly have a placebo effect because, compared with control (CON), the SHAM condition also improved repetitions along with IPC 24,25) . Beaven et al (2012) compared the early (immediate) and late (24 h later) effects of IPC on power production, and they found that IPC showed beneficial effects in both periods 8) .…”
Section: Sprint (Cycle) Performancementioning
confidence: 98%
See 1 more Smart Citation
“…Com o número de estágios realizados, calculamos a distância total percorrida para cada futebolista. Com o propósito de evitar quaisquer efeitos placebo ou nocebo, comuns em estudos com testes de desempenho físico 23,24 as jogadoras não foram informadas sobre o real objetivo do presente trabalho. Apenas foi ressaltado que o objetivo era realizar o melhor desempenho possível nos testes.…”
Section: Yoyo Intermitente Endurance Nível 2 (Yoyoie2)unclassified